2005
DOI: 10.1538/expanim.54.451
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of Steroidogenic Enzymes in the Fetal, Neonatal and Adult Testis of the Shiba Goat

Abstract: Abstract:The localizations of steroidogenic enzymes (P450scc, 3βHSD, P450c17 and P450arom)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 27 publications
(28 reference statements)
4
19
0
Order By: Relevance
“…Fetal testosterone synthesis has been demonstrated in the rat [29,36], sheep [37], pig [38] and goat [15]. Testosterone is essential for male sexual differentiation and growth of male genital organs in the fetal period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fetal testosterone synthesis has been demonstrated in the rat [29,36], sheep [37], pig [38] and goat [15]. Testosterone is essential for male sexual differentiation and growth of male genital organs in the fetal period.…”
Section: Discussionmentioning
confidence: 99%
“…The primary antibodies used in this study are summarized in Table 2. The antibodies against P450scc, P450c17, 3βHSD and P450arom were used in previous studies on testicular steroidogenesis [12,15,18,25,26].For the ABC method, the deparaffinized sections were incubated with methanol containing 0.3% H2O2 for 10 min at room temperature (RT) to block endogenous peroxidase activity and then with normal goat serum (1:50, S-1000, Vector Laboratories) for 30 min at RT to prevent nonspecific staining. The samples were incubated with each primary antibody overnight at 4 C. After an overnight incubation, the secondary antibody, biotinylated anti-rabbit IgG raised in the goat (1:200, BA-1000, Vector Laboratories), was applied for 30 min at RT, and then the sections were incubated with ABC for 30 min at RT (1:2, PK-6100, Vectastain Elite ® ABC Kit, Vector Laboratories).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…18 In the rat, it has been demonstrated that there is a developmentalrelated switch in the cellular location of the main aromatization site, switching from Sertoli cells in sexually immature rats to Leydig cells in mature rats. 11 In contrast, other studies have claimed there is no switch in species such as the stallion, 19 bison, 20 Shiba goat 21 and pig. 22 Interestingly, many seasonal breeding species do exhibit a switch in aromatase localization, however this switch occurs between their breeding and non-breeding seasons including the black bear, 23 sika deer, 24 ground squirrel, 25 bank vole 26,27 and raccoon dog.…”
mentioning
confidence: 89%